2011
DOI: 10.1017/jfm.2011.309
|View full text |Cite
|
Sign up to set email alerts
|

Heat transport by turbulent rotating Rayleigh–Bénard convection and its dependence on the aspect ratio

Abstract: We report on the influence of rotation about a vertical axis on heat transport by turbulent Rayleigh-Bénard convection in a cylindrical vessel with an aspect ratio Γ ≡ D/L = 0.50 (D is the diameter and L the height of the sample) and compare the results with those for larger Γ . The working fluid was water at T m = 40 • C where the Prandtl number Pr is 4.38. For rotation rates Ω 1 rad s −1 , corresponding to inverse Rossby numbers 1/Ro between zero and twenty, we measured the Nusselt number Nu for six Rayleigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 58 publications
8
82
0
Order By: Relevance
“…Read [16] predicted an aspect ratio dependence of the regime transitions for an annulus with internal heating and observed transitions occurring at lower P for higher aspect ratio in numerical simulations. Aspect ratio dependence of transitions between different behaviours has also been seen in Rayleigh-Bénard convection [53]. As the analysis stands P is independent of the height of the fluid.…”
Section: Heat Transfermentioning
confidence: 61%
“…Read [16] predicted an aspect ratio dependence of the regime transitions for an annulus with internal heating and observed transitions occurring at lower P for higher aspect ratio in numerical simulations. Aspect ratio dependence of transitions between different behaviours has also been seen in Rayleigh-Bénard convection [53]. As the analysis stands P is independent of the height of the fluid.…”
Section: Heat Transfermentioning
confidence: 61%
“…11 and 12. At small enough Ro, experiments and direct numerical simulations (DNSs) of the full Navier-Stokes equations (in the Boussinesq approximation) should give similar results as simulations of the asymptotically reduced equations. Up to now, most of the experiments [13][14][15][16][17][18][19][20][21][22][23] and DNSs 16,18,[24][25][26][27] did not reach deep into the rapidly rotating convection regime. The few experimental and numerical studies that entered decisively into this regime 9,[28][29][30] primarily use the overall heat transfer to characterize rapidly rotating Rayleigh-Bénard convection and identify transitions between flow regimes from changes in the heat-flux scaling.…”
Section: Introductionmentioning
confidence: 98%
“…However, all of these investigations were carried out on systems with geometrical constraints in all physical directions, and it is not clear whether the sharp transitions are caused by boundary conditions or whether they would survive in an unconstrained system. Indeed for one of these systems, turbulent rotating Rayleigh-Bénard convection, measurements were made as a function of the lateral extent (aspect ratio) of the system, and it was found that the observed transition moves toward zero rotation rate as the lateral system size approaches infinity [12,11]. Here we report measurements of the heat transport, expressed in terms of the Nusselt number N u, and of the temperature gradient near the center of a cylindrical sample of fluid heated from below and rotated about its vertical axis at a rate Ω.…”
mentioning
confidence: 99%